Koncepcja "głośnej" poezji Mirona Białoszewskiego i jej wpływ na interpretację jego twórczości na przykładzie wiersza "Ja lubię ciemno?" = Miron Białoszewski`s "loud poetry" and its influence on the rest of his works. Based on "Ja lubię ciemno?" - Cudzich-Budniak, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article tackles Miron Białoszewski`s poetry interpretation from audicity`s perspective. What is helpful in the task, is reaching for the original recording of the poem performer by the author for his own use. That recording makes a basis for using such an interpretive tool as sound`s dynamics. The article is also asking the questions if every single text can be read from the perspective of "sound studies" and also with using the tools like sound?s dynamics, and if it always will be justified and valuable.
Keywords: Białoszewski, Miron (1922-1983); intermedialność; badania audialne; dynamika "dźwiękowa"; intermedia lity; sound studiem; dynamics of sound